Precalculus: Concepts Through Functions, A Unit Circle Approach to Trigonometry (3rd Edition)

Published by Pearson
ISBN 10: 0-32193-104-1
ISBN 13: 978-0-32193-104-7

Chapter 8 - Polar Coordinates; Vectors - Section 8.1 Polar Cordinates - 8.1 Assess Your Understanding - Page 592: 81



Work Step by Step

Multiply $1-\cos\theta$ to both sides of the equation to obtain: \begin{align*} (1-\cos\theta)(r)&=\frac{4}{1-\cos\theta} \cdot (1-\cos\theta)\\ r-r\cos\theta&=4\end{align*} Knowing that $r=\sqrt {x^{2}+y^{2}}$ and $r\cos\theta=x$, then the equation above becomes: \begin{align*} \sqrt {x^{2}+y^{2}}-x&=4\\ \sqrt {x^{2}+y^{2}}&=x+4\\ \left(\sqrt {x^{2}+y^{2}}\right)^2&=(x+4)^2\\ x^2+y^2&=x^2+8x+16\\ y^2&=x^2+8x+16-x^2\\ y^2&=8x+16\\ y^2&=8(x+2)\end{align*}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.